Does Mandatory Rotation of Audit Partners Improve Audit Quality? - Lennox, Clive S.; Wu, Xi; Zhang, Tianyu (The Accounting Review, 2014)
ABSTRACT Opponents of mandatory rotation argue that a change of partner is bad for audit quality, as it results in a loss of client-specific knowledge. On the other hand, proponents argue that a change of partner is beneficial, as it results in a positive peer review effect and a fresh perspective on the audit. We test the impact of mandatory partner rotation on audit quality using a unique dataset of audit adjustments in China. Our results suggest that mandatory rotation of engagement partners results in higher quality audits in the years immediately surrounding rotation. Specifically, we find a significantly higher frequency of audit adjustments during the departing partner's final year of tenure prior to mandatory rotation and during the incoming partner's first year of tenure following mandatory rotation.